An Efficient Method for Isolation of Bifidobacteria from Infant Gut - Hung, Nguyen Van; Ha, Bui Thi Viet; Hang, Dinh Thuy (VNU Journal of Science: Natural Sciences and Technology; Vol 32 No 1S, 2016)
Abstract: An efficient method was established for isolation of bifidobacteria from fecal samples of breast-fed infants. The method was based on the combination of Hungate technique applied on anoxic semi-liquid agar tubes, instead of double layer agar plates. Four growth media including BFM, BIM25, MRS and 385 were compared for the isolation efficiency on the basis of Hungate technique. Thus, among 30 isolates obtained from fecal samples of 14 breast fed infants of different ages under 1 year only eight bifidobacteria-like isolates were selected based on cell morphology and fermentation motif. It is revealed that Hungate technique with the use of anaerobic MRS and BFM media was more efficient for isolation of bifidobacteria than that with BIM25 and 385 media. The difference of isolation efficiency in MRS and BFM medium was not obvious. It is therefore recommended that the BFM medium would be applied for isolation of bifidobacteria generally, and in this case, from gut, whereas the MRS medium should be suitable for cultivation and maintaining of pure cultures. In addition, isolation efficiency would also depend on infant’s ages and the way how fecal samples have been stored before isolation.  Keywords: Bifidobacteria, infant gut, Hungate technique, anaerobic growth media.